Respuesta :

Answer:

(-4,-2)

Step-by-step explanation:

first u should chose a variable to eliminate and i choose Y

y=5/2x+8-y=-1/4x-3

get a common denominator

5/2= 10/4

-1/4=-1/4

the equation i will change a little because we are subtracting

10/4x+8+1/4x+3

11/4x+11

solve for the remaining variable which is X

subtract 11 on both sides

0-11=11/4x+11-11

-11=11/4x

multiply both sides by 4/11

-11 times 4/11= 11/4x times 4/11

x=-4

then substitute the variable in one of the equations and i choose y=5/2x+8

5/2(-4)+8= y

-20/2+8= y

-10+8=y

y=-2